Pendampingan dalam Implementasi Strategi Pemasaran Produk Olahan Susu Sapi - Annisa Kesy Garside; Ikhlasul Amallynda (Jurnal SOLMA, 2020)
Usaha Bunda is a small home industry producing several cow’s milk processed products located at Maron village, Pujon Kidul, Malang. The challenge faced by this owner is the marketing aspect to define the right marketing strategy to expand the coverage and increase competitiveness. The goal of this community dedication is to help formulating and implementing the marketing strategy for the Usaha Bunda home industry. The approach is advocation in the form of assistance. Several strategy proposed was consignation with several gift shops and tourist attraction, redesign the product packaging, and creating an online shop. The outcome of assistance in marketing strategy implementation was the owner’s better understanding on the knowledge and skill of product packaging and online marketing. Additionally, the owner also confirmed that there has been an omzet increase of 1.5 to 2 times as the result of the new packaging. The online shop opened at Tokopedia marketplace also helps to expand the product promotion and market coverage without geographical and time limitation.